2023
DOI: 10.1136/rmdopen-2023-003071
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular damage in autoimmune connective tissue diseases: a capillaroscopic analysis from 20 years of experience in a EULAR training and research referral centre for imaging

Abstract: ObjectiveNailfold videocapillaroscopy (NVC) allows the detection of microvascular damage in autoimmune connective tissue diseases (CTDs). The prevalence of the morphological capillary findings was retrospectively evaluated in a wide cohort of patients with Raynaud’s phenomenon secondary to a CTD at the time of the first single NVC, independently from their current treatment, autoantibody profile and comorbidities.MethodsOne-thousand-one-hundred-eighty-one patients affected by CTDs were included from 2001 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…The results confirmed that no specific NVC pattern for SjD can be described as it has been done in adults SjD patients [27][28][29], since no NVC-specific abnormalities (i.e. giant capillaries) or features compatible with a scleroderma pattern or scleroderma-like pattern were detected [43].…”
Section: Discussionsupporting
confidence: 76%
“…The results confirmed that no specific NVC pattern for SjD can be described as it has been done in adults SjD patients [27][28][29], since no NVC-specific abnormalities (i.e. giant capillaries) or features compatible with a scleroderma pattern or scleroderma-like pattern were detected [43].…”
Section: Discussionsupporting
confidence: 76%
“…The clinical history should delve into the patient’s sex, age at onset, patterns of digital involvement (including thumb sparing, symmetricity, and ulcerations), and frequency of RP attacks [ 2 , 42 ]. Additionally, it is crucial to identify potential secondary causes of RP, such as SSc, other autoimmune diseases, hematologic disorders, paraneoplastic conditions, and neurological or vaso-occlusive conditions (as discussed in the clinical manifestation section) [ 5 , 20 , 43 ]. Occupational risk factors like exposure to manual vibrating tools, chemicals (e.g., polyvinyl chloride), medications (e.g., β-blockers and chemotherapy), and smoking history should also be explored [ 23 , 29 , 44 ].…”
Section: Diagnosismentioning
confidence: 99%